Essays on Russia's economic transition - Laura Solanko (Bank of Finland, 2006)
This study comprises an introductory section and three essays analysing Russia's economic transition from the early 1990s up to the present.The papers present a combination of both theoretical and empirical analysis on some of the key issues Russia has faced during its somewhat troublesome transformation from state-controlled command economy to market-based economy. The first essay analyses fiscal competition for mobile capital between identical regions in a transition country.A standard tax competition framework is extended to account for two features of a transition economy: the presence of two sectors, old and new, which differ in productivity; and a non-benevolent regional decision-maker.It is shown that in very early phase of transition, when the old sector clearly dominates, consumers in a transition economy may be better off in a competitive equilibrium. Decision-makers, on the other hand, will prefer to coordinate their fiscal policies. The second essay uses annual data for 1992- 2003 to examine income dispersion and convergence across 76 Russian regions.Wide disparities in income levels have indeed emerged during the transition period.Dispersion has increased most among the initially better-off regions, whereas for the initially poorer regions no clear trend of divergence or convergence could be established.Further, some albeit not highly robust evidence was found of both unconditional and conditional convergence, especially among the initially richer regions.Finally, it is observed that there is much less evidence of convergence after the economic crisis of 1998. The third essay analyses industrial firms' engagement in provision of infrastructure services, such as heating, electricity and road maintenance.Using a unique dataset of 404 large and medium-sized industrial enterprises in 40 regions of Russia, the essay examines public infrastructure provision by Russian industrial enterprises. It is found that to a large degree engagement in infrastructure provision, as proxied by district heating production, is a Soviet legacy.Secondly, firms providing district heating to users outside their plant area are more likely to have close and multidimensional relations with the local public sector.
URN:NBN:fi:bof-201408071691
Keywords: 330; Russia; transition; regional issues; tax competition; infrastructure; Systemtransformation; Steuerwettbewerb; Finanzbeziehungen; Regionale Einkommensverteilung; Infrastrukturinvestition; Öffentliches Unternehmen; Fernwärme; Russland